Couple Relationships Are Associated With Increased REM Sleep—A Proof-of-Concept Analysis of a Large Dataset Using Ambulatory Polysomnography - Drews, Henning Johannes; Drews, Annika (Frontiers in Psychiatry, 2021)
BACKGROUND/OBJECTIVES: Rapid Eye Movement (REM) sleep is associated with memory consolidation and several health effects including stress response, mental health, and longevity. Recently, it has been shown that regularly co-sleeping couples have increased and stabilized REM sleep when co-sleeping as compared to sleeping individually. However, it remained unclear whether this is due to a specific effect of altering the usual sleeping environment by partner deprivation or due to a generalizable REM-sleep promoting effect of couple relationships. The present study aims to clarify this ambiguity. METHODS: Married or never married individuals were taken from the Sleep Heart Health Study (n=5804) and matched regarding sociodemographic and health parameters. Matching was done using propensity score matching (1:1, nearest neighbor) and resulted in two groups of n=69 each (married vs. never married). After confirmation of successful matching, samples were compared regarding REM sleep and other polysomnographic parameters (paired Students t-tests or Wilcoxon signed-rank tests). RESULTS: Married individuals showed significantly higher levels of total and relative REM sleep as compared to never married individuals (all ps ≤ 0.003). Neither other sleep stages nor REM-sleep fragmentation differed between groups (all ps ≥ 0.29). Results regarding number of sleep cycles were ambiguous. CONCLUSION: This is the first between-subjects study to show that couple relationships are associated with increased REM sleep. This finding represents a necessary (but not sufficient) condition for the previously hypothesized self-enhancing feedback loop of REM sleep and sociality as well as for REM-sleep promotion as a mechanism through which couple relationships prevent mental illness.